Enhanced Thermal Stability and Synergistic Effects of Magnesium and Iron Borate Composites against Pathogenic Bacteria. - Ahmad, Pervaiz; Khandaker, Mayeen Uddin; Khan, Abdulhameed; Rehman, Fida; Din, Salah Ud; Ali, Hazrat; Khan, Muhammad Imtiaz; Muhammad, Nawshad; Ahmed, Nasar; Ullah, Zahoor; Khan, Ghulamullah; Haq, Sirajul; et al. (BioMed Research International, 2022)
A simple process based on the dual roles of both magnesium oxide (MgO) and iron oxide (FeO) with boron (B) as precursors and catalysts has been developed for the synthesis of borate composites of magnesium and iron (Mg2B2O5-Fe3BO6) at 1200°C. The as-synthesized composites can be a single material with the improved and collective properties of both iron borates (Fe3BO6) and magnesium borates (Mg2B2O5). At higher temperatures, the synthesized Mg2B2O5-Fe3BO6 composite is found thermally more stable than the single borates of both magnesium and iron. Similarly, the synthesized composites are found to prevent the growth of both gram-positive (Staphylococcus aureus) and gram-negative (Escherichia coli) pathogenic bacteria on all the tested concentrations. Moreover, the inhibitory effect of the synthesized composite increases with an increase in concentration and is more pronounced against S. aureus as compared to E. coli.